PPAR‐γ‐induced changes in visceral fat and adiponectin levels are associated with improvement of steatohepatitis in patients with NASH. (21st July 2021) - Gastaldelli, Amalia; Sabatini, Silvia; Carli, Fabrizia; Gaggini, Melania; Bril, Fernando; Belfort‐DeAguiar, Renata; Positano, Vincenzo; Barb, Diana; Kadiyala, Sushma; Harrison, Stephen; Cusi, Kenneth
Abstract: Background and Aims: Peroxisome proliferator‐activated receptor (PPAR)‐γ agonists decrease hepatic/visceral fat (VF) and improve necroinflammation despite subcutaneous (SC) fat weight‐gain. Understanding the impact of changes in VF, VF‐to‐SC fat distribution (VF/SC) and adiponectin (ADPN) levels in relation to histological improvement after weight‐loss or pioglitazone is relevant as novel PPAR‐γ agonists are being developed for treating non‐alcoholic steatohepatitis (NASH). Methods: Fifty‐five patients with NASH received a −500 kcal/d hypocaloric diet and were randomized (double‐blind) to pioglitazone (45 mg/d) or placebo for 6‐months. Before and after treatment patients underwent a liver biopsy and measurement of hepatic/peripheral glucose fluxes, hepatic/adipose tissue‐IR and, in 35 patients, hepatic and VF/SC‐fat was measured by magnetic resonance spectroscopy/imaging. Data were examined by multivariable statistical analyses combined with machine‐learning techniques (partial least square discriminant analysis [PLS‐DA]). Results: Both pioglitazone (despite weight‐gain) and placebo (if weight‐loss) reduced steatosis but only pioglitazone ameliorated necroinflammation. Using machine‐learning PLS‐DA showed that the treatment differences induced by a PPAR‐γ agonist vs placebo on metabolic variables and liver histology could be best explained by the increase in ADPN and a decrease in VF/SC, and to a lesser degree, improvement in oral glucose tolerance test‐glucose concentrations and ALT. Decrease in steatosis and disease activity score (ballooning plus lobular inflammation) kept a close relationship with an increase in ADPN ( r  = −.71 and r  = −.44, P  < .007, respectively) and reduction in VF/SC fat ( r  = .41 and r  = .37, P  < .03 respectively). Conclusions: Reduction in VF and improved VF/SC‐distribution, combined with an increase in ADPN, mediate the histological benefits of PPAR‐γ action, highlighting the central role of fat metabolism and its distribution on steatohepatitis disease activity in patients with NASH.